The scientific discourse in Islamic civilization and postmodernism - Ahmed Shogar, Ibrahim Adam (2011)
Although Muslim intellectuals believe that Islam is a global religion which contains many of universal values, but they are skeptic about many of the western oriented ideological forces, such as modernism, postmodernism, and globalization. Islamic civilization has exerted great efforts for the advancement of science and practical knowledge. However, science in Islam declined for many, internal and external factors. The mainstream of revival discourse of Muslim intellectuals throughout the history of Islam was culminated by certain works, such as “Revival of Religious Sciences” of Imam al-Ghazali and “Reconstruction of Religious Thought” of Igabal. All such efforts were reflection of their own periods of time that characterized by certain historical, cultural, and global factors which dictate the intellectual discourse. Many key concepts of scientific discourse have been emerging in the community of Muslim intellectuals of the modern world, especially since 1970s. Intellectual reformation, Islamic Science, Islamization and Integration of knowledge, reconstruction of Muslim mind, are the basic topics of the scientific discourse in last few decades. Western oriented ideologies such as modernity, postand modernity are main factors behind this new direction of the scientific discourse in Islamic civilization. The main objective of the article is to examine this new trend of the Islamic intellectual discourse and its impacts on the entire process of Islamic revivalism, especially in the period of the changeable world of globalization.